Trinidad and Tobago : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1997)
This Selected Issues paper on Trinidad and Tobago highlights that real GDP growth accelerated slightly from 2.4 percent in 1995 to 3.2 percent in 1996. In both years, growth was mainly driven by a good performance of the non-oil sector, which expanded by 3 percent and 3.6 percent, respectively. Construction, distribution, and tourism grew at an especially rapid pace. Manufacturing showed an uneven performance, growing in 1995, but stagnating in 1996, which was owing to the differential effects of trade liberalization on its various subsectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet